2020
DOI: 10.1002/aocs.12452
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Oilseeds Native to Amazon and Brazilian Cerrado Biomes: Benefits, Chemical and Functional Properties, and Extraction Methods

Abstract: The primary objective of this study was to shed greater light on the characteristics and multifaceted potential of oil extracts from kernels of Bertholletia excelsa (Brazil nut), seeds of the Plukenetia species and Caryocar species. These are but a few of the multitude of the plant species found in the Amazon and Brazil's Cerrado biomes. They have many substantial organoleptic, nutritional, and functional properties that are comparable or exceed better known oils, and they manifest health benefits and prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 110 publications
(186 reference statements)
0
8
0
Order By: Relevance
“…This difference in the fatty acid profile may be associated with the polarity of the solvent used and the temperature of the extraction process, as high temperatures accelerate the lipid degradation process (Cornelio-Santiago et al, 2021;Cornelio-Santiago, Mazalli, et al, 2019). The proportion of fatty acid profiles found ( were also identified, such as PLLn (max.…”
Section: Determination Of the Fatty Acid Profile And Probability Of T...mentioning
confidence: 99%
See 1 more Smart Citation
“…This difference in the fatty acid profile may be associated with the polarity of the solvent used and the temperature of the extraction process, as high temperatures accelerate the lipid degradation process (Cornelio-Santiago et al, 2021;Cornelio-Santiago, Mazalli, et al, 2019). The proportion of fatty acid profiles found ( were also identified, such as PLLn (max.…”
Section: Determination Of the Fatty Acid Profile And Probability Of T...mentioning
confidence: 99%
“…The extraction processes of commercial soybean oil are well established and use organic solvent extraction (hexane) as the extraction process with the highest yield, reaching 99% of the oil contained in the oilseeds. This extraction consists of a mass transport process between the solvent and the matrix until the concentration equilibrium is reached (Cornelio‐Santiago et al, 2021; Shahidi, 2005). The solvent used in the extraction is hexane, derived from petroleum, considered to be neurotoxic, with the property of generating explosive mixtures in contact with atmospheric air and, according to the US Occupational Safety and Health Administration (OSHA, 2022), with a daily exposure limit for humans of 500 ppm (CDC, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to the studies by Nimet et al (2011) and Rai et al (2016), who described the use of gas chromatography to determine the TFA profile in sunflower oil extracted using supercritical carbon dioxide (scCO 2 ), the extraction method did not influence the TFA profile, as was observed in coffee oil extraction ( Cornelio-Santiago et al, 2017 , De Oliveira et al, 2014 ). However, in Brazil nuts, Cornelio‐Santiago et al (2021) found differences in fatty acid content depending on how the oil was extracted.…”
Section: Introductionmentioning
confidence: 95%
“…The Brazil nut is a brown fruit generally cultivated in the Amazon [ 30 ]. Its oil is an interesting object of study, since it has between 60.8% and 72.5% lipids [ 30 , 31 ]. Among them, it has 75.6% unsaturated fatty acids (UFA) [ 30 ], and both monounsaturated (MUFA) and polyunsaturated (PUFA), which means a significant amount of double bonds that allow its functionalization by chemical processes such as maleinization.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, hemp seed oil is also attractive for this purpose, as it is high in linoleic acid (55.3%) and linolenic acid (20.3%) [ 32 ]. Both allow their oil to be extracted by cold pressing with a good yield and also have good oxidative stability [ 31 , 33 ]. Thereupon, this work evaluates the potential of MBNO and MHO as a bio-based plasticizer to improve the ductile properties of PLA related to its brittleness and the comparison of these with commercial maleinized linseed oil (MLO).…”
Section: Introductionmentioning
confidence: 99%